Pendampingan Penulisan Puisi Epigram untuk Menumbuhkan Minat dan Kemampuan Menulis Puisi Siswa di Sekolah SMP Alam Al Fath Jambi - H, Helty; Izar, Julisah; W, Warni; Afria, Rengki; Harianto, Neldi (Yayasan Daarul Huda Kruengmane, 2024)
The purpose of implementing Community Service activities at SMP ALAM AL FATH Jambi is to provide assistance and knowledge to students in fostering interest, ability and entrepreneurial spirit in producing literary works in the form of epigram poetry. Where the topics of assistance are: the definition of epigram poetry, the function of epigram poetry, the characteristics of epigram poetry and techniques in writing epigram poetry. To foster interest, ability and entrepreneurial spirit in producing literary works in the form of epigram poetry, assistance and training in writing epigram poetry will be carried out, where later literary works will be produced in the form of a collection or anthology of epigram poetry by students at SMP ALAM AL FATH Jambi. This literary work will also be ISBNed and will be published in the National Library and can be traded publicly.